Numerical Evaluation Of Effectiveness Of Drainwells In Dewatering Overburden At Surface Coal Mines - R. L. Howell; L. C. Atkinson (Society for Mining, Metallurgy & Exploration, 2000)
Typical sedimentary sequences overlying coal seams consist of interbedded sandstones, siltstones, shales, and rider coal seams. In many surface coalmine settings, these sediments are saturated; and prior dewatering of them is necessary for effective and economic mining, including the stacking of saturated spoils. Such sedimentary sections usually have a very low vertical hydraulic conductivity that does not allow them to drain in a timely manner prior to their being stripped. One potential solution is installation of drainwells. Drainwells are small diameter wells that can collect water laterally from the various more permeable layers in the overburden and then gravity drain it to a lower layer – often the coal seam being mined – where it can be removed by pumping wells or sumps located in the bottom of the pit. A ground-water flow model utilizing the 3-dimensional finite element code MINEDW has been used to evaluate the effectiveness of usingdrainwells in a hydrogeologic setting that is typical of the Powder River Basin. A series of numerical simulations were completed using various combinations and spacings of drainwells and pumping wells to dewater the overburden and coal seams. The numerical simulations suggest that drainwells can be a very effective method of overburden dewatering.